Balance and Gait Improvements of Postoperative Rehabilitation in Patients with Parkinson's Disease Treated with Subthalamic Nucleus Deep Brain Stimulation (STN-DBS). (4th August 2019) - Sato, Kazunori; Aita, Noriaki; Hokari, Yoshihide; Kitahara, Eriko; Tani, Mami; Izawa, Nana; Hatori, Kozo; Nakamura, Ryota; Sasaki, Fuyuko; Sekimoto, Satoko; Jo, Takayuki; Oyama, Genko; et al.
Abstract : Background . Deep brain stimulation of the subthalamic nucleus (STN-DBS) is a surgical treatment to reduce the "off" state motor symptoms of Parkinson's disease (PD). Postural instability is one of the major impairments, which induces disabilities of activities of daily living (ADLs). The effectiveness of STN-DBS for postural instability is unclear, and the effect of rehabilitation following STN-DBS has remained uncertain. Objective . The purpose of this study was to examine changes in balance ability, gait function, motor performance, and ADLs following 2 weeks of postoperative rehabilitation in PD patients treated with STN-DBS. Methods . Sixteen patients were reviewed retrospectively from February 2016 to March 2017. All patients were tested in their "on" medication state for balance and gait performance using the Mini-Balance Evaluation Systems Test (Mini-BESTest) and the Timed "Up and Go" (TUG) test before the operation, after the operation, and during the discharge period. The UPDRS motor score (UPDRS-III) and Barthel Index (BI) were assessed before the operation and during the discharge period. Rehabilitation focused on muscle strengthening with stretching and proactive balance training. Friedman's test and the post hoc Wilcoxon's signed-rank test were used to analyze the balance assessments, and ANOVA and the post hoc Tukey's test were used to analyze gait performance. The significance level wasp < 0.05 . Results . During the discharge period, the Mini-BESTest and TUG were significantly improved compared with the preoperative and postoperative periods (p < 0.05 ). There were no differences between preoperative and postoperative periods in the Mini-BESTest (p = 0.12 ) and TUG (p = 0.91 ). The BI and motor sections of the UPDRS did not differ significantly between the preoperative and postoperative periods (p = 0.45, p = 0.22 ). Conclusion . The results of this study suggest that postoperative rehabilitation improves balance and gait ability in patients with PD treated with STN-DBS.